Laboratory cum glasshouse laboratory screening methods for the evaluation of sugarcane varieties against borer pests - Punithavalli, M; Mohanraj, K; Salin, K P (Indian Journal of Plant Protection, 2025)
Laboratory cum glasshouse screening methods were developed at the ICAR-Sugarcane Breeding Institute in Coimbatore, Tamil Nadu, India, to evaluate sugarcane varieties derived from the genera Saccharum and Erianthus for their resistance/susceptibility to borer pests. The results revealed that all the varieties were severely infested by early shoot borer (ESB), with an incidence ranging from 86 to 100%. No significant differences in ESB incidence were observed among Saccharum and Erianthus introgressed varieties. However, sugarcane varieties survivability after ESB infestation differed significantly. Erianthus introgressed varieties showed a higher survival rate than Saccharum introgressed varieties. Similarly, internode borer (INB) incidence differed significantly, with Erianthus-introgressed varieties (Co 06030 and Co 06022) exhibiting lower INB incidence compared to the Saccharum-introgressed varieties. The results also indicated that INB-fed internodes have more than one larva per plant in Saccharum introgressed varieties and less than one larva per plant in Erianthus introgressed varieties. Furthermore, INB-affected internode tunnels were longer in Saccharum introgressed varieties like Co 11015 and Co 86032, whi they were shorter in Erianthus introgressed varieties such as Co 06022 and Co 06030. The study identified two varieties, Co 06022 and Co 06030, derived from an Erianthus background, as showing resistance to both ESB and INB. In contrast, one variety, Co 86032, from a Saccharum background, demonstrated resistance to ESB. The study explored potential laboratory screening methods to assess sugarcane varieties for resistance or susceptibility to borer pests, aiding in the identification of confirmed resistant and susceptible varieties.